Perancangan Sistem Informasi Akuntansi Realisasi Anggaran Pada Kantor Badan Pelayanan Perizinan Terpadu (BPPT) Jawa Barat Menggunakan Microsoft Visual Basic 2008 Dan Database MySQL Server - Rizki Rinaldi; Dony Waluya Firdaus (Labkat Press KA FTIK UNIKOM, 2017)
Badan Pelayanan Perizinan Terpadu (BPPT) Jawa Barat that have an address at Jl. PHH Mustofa No. 22 Bandung. Is a govermment agency that is engaged in licensing services. Problems that occur is a recording system that is still done manually so in the execution of recording to the financial statements do relatively long because it susceptible to errors in recording data. So that the problems that occur can be minimized, the authors take the title research â€œAccounting Information System Design Actual Budgeting on Badan Pelayanan Perizinan Terpadu (BPPT) Jawa Barat by Using Microsoft Visual Basic 2008 and MySQL Database Serverâ€. The type of research use an academic research, the types of data use the qualitative data, the type of study design use descriptive, surveys, and primary secondary data, survey research method, data collection techniques use is a field research, consisting of interviews, system development method use process-oriented methodology, data and output. The structure of the development of the system use was iterations. Information system use context diagram, data flow diagrams, and flowcharts.